2022
DOI: 10.1002/adma.202205881
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Powered, Implantable, and Wirelessly Controlled NO Generation System for Intracranial Neuroglioma Therapy

Abstract: Gas therapy is an emerging technology for improving cancer therapy with high efficiency and low side effects. However, due to the existence of the gatekeeper of the blood–brain barrier (BBB) and the limited availability of current drug delivery systems, there still have been no reports on gas therapy for intracranial neuroglioma. Herein, an integrated, self‐powered, and wirelessly controlled gas‐therapy system is reported, which is composed of a self‐powered triboelectric nanogenerator (TENG) and an implantabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…32,33 It has been reported that light, heat, or some metal ions could induce the S-N bond cleavage and cause NO to be released from GSNO. [34][35][36][37][38] Thus, the high photothermal conversion effect of BP provides a basis for the breakage of the S-N bond. To test this, 4, 5-diamino fluorescein (DAF-2) was used as an indicator to detect the released NO from the BN-MSs.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 It has been reported that light, heat, or some metal ions could induce the S-N bond cleavage and cause NO to be released from GSNO. [34][35][36][37][38] Thus, the high photothermal conversion effect of BP provides a basis for the breakage of the S-N bond. To test this, 4, 5-diamino fluorescein (DAF-2) was used as an indicator to detect the released NO from the BN-MSs.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [85] Copyright 2022, Wiley-VCH. (d) The structure of UP-TTD and its mechanism of tumor therapy.…”
Section: Ng As a Power Source For The Cancer Therapymentioning
confidence: 99%
“…(wsTENG) with single-electrode mode. [85] The wsTENG could be attached to human body to collect energy from movement (Figure 3c). A NO releasing device (NO-LED) implanted transcranial close to tumor tissue was powered by the generated energy from wsTENG.…”
Section: Ng As a Power Source For The Cancer Therapymentioning
confidence: 99%
“…The triboelectric nanogenerator (TENG) has become a promising candidate for the next generation of energy harvesting [ 1 , 2 ] and self-powered sensing platforms [ 3 , 4 , 5 , 6 ]. It possesses outstanding characteristics such as high energy conversion efficiency [ 7 , 8 ], abundant materials resource [ 9 , 10 ], a simple fabrication process [ 11 , 12 ] and multifunctional integration [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%